Cultural perspectives on children’s tadpole drawings: at the interface between representation and production - Gernhardt, Ariane; Rübeling, Hartmut; Keller, Heidi (Frontiers in Psychology, 2015)
This study investigated tadpole self-drawings from 183 three-to-six years old children living in seven cultural groups, representing three ecosocial contexts. Based on assumed general production principles, the influence of cultural norms and values upon specific characteristics of the tadpole drawings was examined. The results demonstrated that children from all cultural groups realized the body-proportion effect in the self-drawings, indicating universal production principles. However, children differed in single drawing characteristics, depending on the specific ecosocial context. Children from Western and non-Western urban middle-class contexts drew themselves rather tall, with many facial features, and preferred smiling facial expressions, while children from rural traditional contexts depicted themselves significantly smaller, with less facial details, and neutral facial expressions.